2016
DOI: 10.1016/j.coldregions.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of ice-induced loads and responses of a monopile-type offshore wind turbine in parked and operating conditions

Abstract: Offshore wind is an attractive source of renewable energy. In regions with cold climates, such as Canada, the Baltic Sea, and Bohai Bay, a good understanding of ice loads is essential to design a reliable and cost effective support structure for an offshore wind turbine. This paper presents a study of the dynamic ice-structure interaction of a commonly used monopile-type offshore wind turbine in drifting level ice in both parked and operating conditions. A semi-empirical numerical model for ice-structure inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…This paper investigates the FL of a 5‐MW wind turbine model with properties provided by the US National Renewable Energy Laboratory (NREL) . Various studies have been based on this wind turbine as a significant amount of data is available for it . In this study, different software packages were used for the fatigue analysis, as shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper investigates the FL of a 5‐MW wind turbine model with properties provided by the US National Renewable Energy Laboratory (NREL) . Various studies have been based on this wind turbine as a significant amount of data is available for it . In this study, different software packages were used for the fatigue analysis, as shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…30 Various studies have been based on this wind turbine as a significant amount of data is available for it. [31][32][33][34][35][36][37] In this study, different software packages were used for the fatigue analysis, as shown in Figure 1. The preprocessing module TurbSim was used to model the turbulent incoming wind field as an input to FAST.…”
mentioning
confidence: 99%
“…Some researchers focus on the predictions of the coupled dynamic loads and responses of an OWT [2,21]. Shi et al studied the dynamic ice-structure interaction of a monopile-type OWT in drifting level ice in both parked and operating conditions by coupling a semi-empirical numerical model to the aero-hydro-servo-elastic simulation tool HAWC2 [22]. The effects of ice drifting speed and ice thickness were investigated by using the coupled dynamic analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of response of a wind turbine on the ice loads was not included in the model. Shi et al (2016) developed a simulation program for ice force coupled with the software HAWC2 to study the dynamic effect of ice sheets on the foundation of offshore wind turbines [28]. However, the present method can only be applied to calculate the ice bending load.…”
Section: Introductionmentioning
confidence: 99%
“…To extend the proposed method by Shi et al (2016), the scope of this study aims to improve the dynamic ice-structure interaction model and develop an ice load analysis program to be used for cylindrical and nearly vertical structures. The updated program is used to simulate the non-simultaneous crushing force acting on the cylindrical structures of wind turbines.…”
Section: Introductionmentioning
confidence: 99%